HUBUNGAN RIWAYAT PAPARAN PESTISIDA DENGAN TEKANAN DARAH PADA PETANI PENYEMPROT DI DESA SUMBEREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Kusuma Dara Zulfania; Onny Setiani; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Magelang is one of the districts in Central Java with a high rate of pesticide use, most of which is agriculture. From the preliminary study found systolic blood pressure ranged from 110-163 mmHg with an average of 142 mmHg and diastolic blood pressure ranged from 70-91 mmHg with an average of 85 mmHg in 10 farmers, and the researchers found some of the symptoms that farmers often complain of because of dizziness, nausea, numbness, and blurred vision. The purpose of this study was to determine the relationship between the history of exposure to pesticides with blood pressure in sprayer farmers in Sumberejo Village District Ngablak, Magelang. This research is an analytic survey research with cross-sectional approach. Data were obtained through interviews using questionnaires, blood cholinesterase examination, and blood pressure measurements in auscultation of 43 sprayer farmers. Data were analyzed using Chi-Square test. The variables observed were history of pesticide exposure, length of service, duration of work per day, frequency of spray, use of personal protective equipment, blood cholinesterase level. The result of statistical test shows that there is correlation on the variable of pesticide exposure history to systolic pressure (p=0,001), and diastolic (p-value=0,050), on the variable length of service to systolic pressure (p=0,017) and diastolic pressure (p= 0,015), also on variables of blood cholinesterase to systolic pressure (p = 0.041). There is no correlation to the variable of working duration against systolic pressure (p = 0,120), and diastolic pressure (p = 0.637), at variable of spraying frequency to systolic pressure (p = 0,960) and diastolic (p = 0173), on variable of APD usage to systolic pressure (p = 0,864) and diastolic (p = 0,864), and variable of cholinesterase level at diastolic pressure (p = 0.365). From this research, it is suggested to have periodic cholinesterase and blood pressure checks on farmers by health workers.